Analytical Method Development for the Determination of Α-Endosulfan and Bifenthrin Pesticide Residues in Tea - Dyah Styarini; Andreas Andreas; Y. Susanto Ridwan; Retno Yusiasih (Indonesian Journal of Chemistry, 2014)
The development of analytical method for the determination of α-endosulfan and bifenthrin residues in tea has been done. The complex matrices and also the pigment were the challenge in doing quantification of the pesticide residues in tea matrices. In order to get appropriate analysis method for the determination of pesticide residues in tea, the modification was done in the analytical method for the determination of organochlorine multiresidue in non fat matrices: seasoning and spicy that is published by Directorate General of Food Crops, Directorate of Food Plant Protection. The modification was done particularly in clean-up step to remove the interferences from the extract of tea matrices such as the pigment that usually interfere the measurement with Gas Chromatography (GC). The result showed that the MDL value for both analytes were 0.5 ng/g that were much lower than MRLs. The percent recovery obtained from the method was 78.58 and 90.19% for α-endosulfan and bifenthrin, respectively. The precision of the analysis method for both analytes were good since the % RSD values were below than the Horwitz’s value that was 19.18% at spiking level concentration of 300 ng/g.